The Hike in BPJS Kesehatan’s Premiums based on The principle of Justice in Service Regulation of Healthcare Insurance - Alfin Reza Syahputra; Adis Imam Munandar (LAW REFORM, 2021)
There have been a lot of complaints regarding the service received by the members of Healthcare and Social Security Administrative Body, or so called BPJS Kesehatan. This situation has been worsened with the hike in premiums of BPJS Kesehatan’s independent members stipulated in Presidential Regulations Number 75 / 2019 and The Amendment of Presidential regulation Number 82/2018 on Health insurance. After announcing the hike of BPJS Kesehatan premiums, the government must also improve the healthcare service to all the independent participants of BPJS Kesehatan. This study aimed to examine juridical review on the hike in BPJS’s Premiums based on the principle of justice on the policies of healthcare and social security. This study was conducted by applying normative juridical research method using statue approach and secondary data. According to the result of the research, Regulation Number 40 Year 2004 concerning National Social Insurance and Regulation Number 24 Year 2011 on the implementing agency of social insurance have applied the principle of justice in their policies. However, Presidential Regulation Number 75 Year 2019 “Presidential Regulation Number 82 Year 2018 on Health Insurance” has not implemented or reflected the principle of justice in its policies. In addition, the government reason to increase the payment of BPJS Kesehatan is that BPJS has been in financial deficit. In order to solve this problem, one of the solutions that the government can offer is to seek for other financial sources instead of putting the burden on the members of the social health insurance program.